2013
DOI: 10.1073/pnas.1301900110
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural landscape simplification does not consistently drive insecticide use

Abstract: The increase in agricultural production over the past 40 y has greatly altered land-use patterns, often resulting in simplified landscapes composed of large swaths of monocultures separated by small fragments of natural lands. These simplified landscapes may be more susceptible to insect pest pressure because of the loss of natural enemies and the increased size and connectivity of crop resources, and a recent analysis from a single year (2007) suggests this increased susceptibility results in increased insect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 30 publications
3
58
1
1
Order By: Relevance
“…Data used in this study includes 1997, 2002, 2007, and 2012 census years, and includes the following county-level variables: land area treated with insecticides, market value of all crops, total land area, total agricultural land area, total harvested area, and harvested acres of specific crops. All are in acres, as given the the COA, except for crop value which were converted to US dollars/hectare to be consistent with previous studies (Larsen, 2013;Meehan et al, 2011).…”
Section: Methodsmentioning
confidence: 60%
See 2 more Smart Citations
“…Data used in this study includes 1997, 2002, 2007, and 2012 census years, and includes the following county-level variables: land area treated with insecticides, market value of all crops, total land area, total agricultural land area, total harvested area, and harvested acres of specific crops. All are in acres, as given the the COA, except for crop value which were converted to US dollars/hectare to be consistent with previous studies (Larsen, 2013;Meehan et al, 2011).…”
Section: Methodsmentioning
confidence: 60%
“…Two recent studies that applied different statistical methods on the same variable sets have drawn controversial conclusions regarding the effect of landscape simplification on insecticide use intensity, using the proportion of cropland treated with insecticides as a proxy for "use intensity" (Larsen, 2013;Meehan et al, 2011). While Larsen (2013) used ordinary least squares and Meehan et al (2011) used spatial error models, they both found that in 7 Midwest states, i.e. Illinois, Indiana, Iowa, Michigan, Minnesota, Ohio, and Wisconsin, 1) the proportion of corn acreage and 2) the proportion of fruits and vegetables in total harvested cropland of a county both significantly correlated to increased insecticide use in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data-driven approaches have proven useful in elucidating the larger scale patterns in the relationship between landscape-level agricultural intensification and insecticide use (18,19). However, these studies have been limited in spatial resolution of both crop (20) and insecticide data (21).…”
mentioning
confidence: 99%
“…Moreover, effects of insecticide input on bio-control can go beyond farm level (Bianchi, Ives, and Schellhorn 2013). For example, crop pest abundance increases with the proportion of harvested cropland treated with insecticides in Midwestern United States (Meehan et al 2011), although this relationship can vary greatly between years (Larsen 2013).…”
Section: Local Effectsmentioning
confidence: 99%